New data on the Holocene evolution of the Dvina Bay (White Sea) - Novichkova, Ye. A.; Reikhard, L. Ye.; Lisitzin, A. P.; Rybalko, A. Ye.; De Vernal, A. (Doklady Earth Sciences, 2017)

A New Chronology of Late Quaternary Sequences From the Central Arctic Ocean Based on “Extinction Ages” of Their Excesses in^231 Pa and^230 Th - Hillaire‐Marcel, C.; Ghaleb, B.; De Vernal, A.; Maccali, J.; Cuny, K.; Jacobel, A.; Le Duc, C.; McManus, J. (Geochemistry, Geophysics, Geosystems, 2017)
Abstract Merging the late Quaternary Arctic paleoceanography into the Earth's global climate history remains challenging due to the lack of robust marine chronostratigraphies. Over ridges notably, low and variable sedimentation rates, scarce biogenic remains ensuing from low productivity and/or poor preservation, and oxygen isotope and paleomagnetic records differing from global stacks represent major impediments. However, as illustrate here based on consistent records from Mendeleev‐Alpha and Lomonosov Ridges, disequilibria between U‐series isotopes can provide benchmark ages. In such settings, fluxes of the particle‐reactive U‐daughter isotopes 230 Th and 231 Pa from the water column, are not unequivocally linked to sedimentation rates, but rather to sea‐ice rafting and brine production histories, thus to the development of sea‐ice factories over shelves during intervals of high relative sea level. The excesses in 230 Th and 231 Pa over fractions supported by their parent U‐isotopes, collapse down sedimentary sequences, due to radioactive decay, and provide radiometric benchmark ages of approximately 300 and 140 ka, respectively. These “extinction ages” point to mean sedimentation rates of ∼4.3 and ∼1.7 mm/ka, respectively, over the Lomonosov and Mendeleev Ridges, which are significantly lower than assumed in most recent studies, thus highlighting the need for revisiting current interpretations of Arctic lithostratigraphies in relation to the global‐scale late Quaternary climatostratigraphy. , Plain Language Summary The Arctic Ocean represents a major component of the Earth climate system notably with regard to the Arctic amplification and freshwater fluxes toward the global ocean. Understanding its role versus the global climate history of the recent glacial/interglacial cycles remains challenging due to the lack of robust chronology of marine sedimentary archives. In the present study, we demonstrate that the decay of Uranium series isotopes in sediments from major Arctic ridges provide benchmark ages for the last ∼300,000 years and support the concept of a “sediment‐starved” environment in the central Arctic Ocean. , Key Points New chronology of late Quaternary marine sequences from the central Arctic Mean sedimentation rates of the order of millimeters per thousand years over ridges Highly discontinuous ice‐rafted sedimentation over ridges with gaps

Svalbard ice-sheet decay after the Last Glacial Maximum: New insights from micropalaeontological and organic biomarker paleoceanographical reconstructions - Rigual-Hernández, A.S.; Colmenero-Hidalgo, E.; Martrat, B.; Bárcena, M.A.; De Vernal, A.; Sierro, F.J.; Flores, J.A.; Grimalt, J.O.; Henry, M.; Lucchi, R.G. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2017)

Greenland Ice Sheet mass loss rate will exceed Holocene values this century - Briner, J. P.; Cuzzone, J. K.; Badgeley, J.; Allan, E.; Bennike, O.; Cluett, A.; Csatho, B. M.; de Vernal, A.; Downs, J.; Hakim, G. J.; Johnson, J. V.; Larour, E. Y.; et al. (2019)
The Greenland Ice Sheet (GrIS) is a major contributor to sea level rise and may already be in irreversible decline. Observations spanning recent decades show the GrIS losing mass at an increasing rate; however, projecting this trend into the future is complicated by year-to-year variability and requires looking at longer timescales. Historical data suggest the GrIS was nearly in balance in the 1800s (-900 Gt/century), but had negative balance in the 1900s (-4000 to -8000 Gt/century). Projecting observations made thus far from the 2000s, mass-loss rate could average anywhere from ca. -40,000 to -100,000 Gt/century. Our goal is to evaluate these historic and contemporary rates of GrIS mass loss within the framework of the current Holocene interglacial spanning the last 12,000 years. To do so we combine the first highly resolved paleo-GrIS simulations using NASA's Ice Sheet System Model with novel climate forcing based on a data assimilation approach using multiple paleoclimate records. Our new simulations take place across a glaciologically simple domain in SW Greenland (encompassing ca. 30% of the ice sheet), where they are validated with our detailed glacial chronology of Holocene ice margin change. During the Holocene thermal maximum, a period between ca. 10,000 and 8000 years ago, the GrIS experienced elevated mass loss rates, with maximum values on the order of -5000 to -10,000 Gt/century for our model domain. When these values are scaled to the entire GrIS (using the proportion of SW mass loss vs. total GrIS mass loss from contemporary studies), they equate to maximum mass loss rates of ca. -20,000 to -40,000 Gt/century. From this we conclude that the rate of GrIS mass loss will exceed Holocene values this century.
Conference Name: AGU Fall Meeting Abstracts ADS Bibcode: 2019AGUFM.C11B..06B
Keywords: 0726 Ice sheets; 1616 Climate variability; 1621 Cryospheric change; 1641 Sea level change; CRYOSPHERE; GLOBAL CHANGE